Full utilization of section in prestressed concrete composite beams based on shift in neutral axis - Rao, A. Sreenivasa; Reddy, N. Ravindra (Journal of Structural Engineering, 2025)
Conventional procedures for flexural design of composite beams start with an assumed value for the ratio of the bottom section modulus of the composite beam and that of precast beam. A novel method that does away with this practice and instead concentrates on the neutral axis shift is proposed in this paper. A new procedure utilizing the full section for the flexural design of composite beams in prestressed concrete is presented. Two numerical examples are also presented to illustrate the proposed method. For the example-I considered, the saving realized using the proposed method over a recently published procedure is as much as 36 percent which is substantial. This method is more rational and the designed section is economical.